Constitutional justice and political process: the tendencies of interaction and search for the doctrine - Jarašiūnas, Egidijus (Politologija, 1999)
In this article, the problems of the interaction of constitutional justice, which is the main institution of constitutional protection, and the political process are dealt with. At the junction of law and politics, it is very important to define the possible limits of the action of the Constitutional Court and to guarantee that the Court, deciding the constitutionality issues of legal decisions of the institutions of power, should assess their conformity to the Constitution but never whether these decisions were rational or suitable. The interaction of law and politics is accounted for by various doctrines. The most outstanding among them is the "political questions" doctrine, under which the courts should shun decisions of clearly political questions. However, it is not always possible to apply this doctrine in the European model of constitutional justice. The "politics under the rule of law" doctrine advanced by L. Favoreu, the leader of the Aix school (École d’Aix), might serve for a better understanding of the place of constitutional justice in the complex system of political relations. Placement of the political process into the frames of law is a reality that should not be unaccounted for when one speaks of the relation between law and politics. In the article, some aspects of the process of the placement of the political process into the frames of law are analyzed. The best proof of this process is constitutional justice itself. The increase of the significance of the Constitution and law in political life is shown by such circumstances: formation of the constitutional culture, the trend of the transfer from political language to legal language, increase of the weight of the legal argumentation in political debates, frequent petitions of politicians concerning the settlement of constitutional disputes, recognition of the proceedings at the Constitutional Court as a new phase of decision-making, etc. This shows the shift in the nature of political life. Possible counter-arguments are also analyzed in the article: the aforementioned circumstances confirm not the placement of the political process into the frames of law but the politicization of law. Even such a view, however, does not deny the impact of constitutional justice on the nature of political life. What are the perspectives of politics under the rule of law in the society of young democracy? Its future might be associated with the increase of strength of law and lawfulness in all areas of life. In the opinion of the author, the establishment of the "politics under the rule of law" doctrine might serve as a sufficient basis for the Constitutional Court investigating cases in the context of complex political relations.